Analysis of Review of Financial Accounting Standards for Micro, Small and Medium Entities at "Kopi Kampus" Jember - Muhammad Rijalus Sholihin; Leonita Cicilia; Mustafa Samir; Nilam Sabrina; Yupita Keke Hartono; Endang Sriwahyu Arini (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
Financial Reports are records of financial information from a company in an accounting period. The existence of financial reports can be used to describe company performance, especially in the financial sector. The aim of this research is to determine the extent of implementation of SAK EMKM in MSMEs, analyze MSME financial reports, and identify the advantages and disadvantages of recording financial reports at the Kopi Kampus cafe. The research method used is descriptive qualitative, by interviewing business owners and analyzing financial reports that have been prepared for Kopi Kampus. The research results provide information that Kopi Kampus has not fully implemented SAK EMKM, but has used an Accounting Information System in the form of the Microsoft Excel application. In recording financial reports, business owners ask for help from personnel whose professional level is unknown, so that there are irregularities in their financial reports in the form of taxes. Overall, Kopi Kampus has been quite detailed in recording its financial reports even though it has not fully implemented SAK EMKM